Trust the Police? Self-Selection of Motivated Agents into the German Police Force - Guido Friebel; Michael Kosfeld; Gerd Thielmann (Institute of Labor Economics (IZA), 2016)
We conduct experimental games with police applicants in Germany to investigate whether intrinsically motivated agents self-select into public service. Our focus is on trustworthiness and the willingness to enforce norms as key dimensions of intrinsic motivation in the police context. We find that police applicants are more trustworthy than non-applicants, i.e., they return higher shares as second-movers in a trust game. Furthermore, they invest more in rewards and punishment when they can enforce cooperation as a third party. Our results provide clear evidence for advantageous self-selection into the German police force, documenting an important mechanism by which the match between jobs and agents in public service can be improved.
Keywords: C9; D64; D73; J45; 330; self-selection; intrinsic motivation; public service; trustworthiness; norm enforcement